Molecular dynamics of carboxymethyl ?/?-hybrid carrageenan films doped with NH4I - Torres F.G. (2019)
This work was supported by the Vice-Rectorate for Research of the Pontificia Universidad Católica del Perú, the National Council of Science, Technology and Technological Innovation of Peru (CONCYTEC/FONDECYT) and The National Innovation Program for Competitiveness and Productivity (INNOVATE-PERU) of the Peruvian Ministry of Production.